ICTV Virus Taxonomy Profile: Geminiviridae - Zerbini, F Murilo; Briddon, Rob W; Idris, Ali; Martin, Darren P; Moriones, Enrique; Navas-Castillo, Jesús; Rivera-Bustamante, Rafael; Roumagnac, Philippe; Varsani, Arvind; Ictv Report Consortium (Journal of general virology, 2017)
The geminiviruses are a family of small, non-enveloped viruses with single-stranded, circular DNA genomes of 2500-5200 bases. Geminiviruses are transmitted by various types of insect (whiteflies, leafhoppers, treehoppers and aphids). Members of the genus Begomovirus are transmitted by whiteflies, those in the genera Becurtovirus, Curtovirus, Grablovirus, Mastrevirus and Turncurtovirus are transmitted by specific leafhoppers, the single member of the genus Topocuvirus is transmitted by a treehopper and one member of the genus Capulavirus is transmitted by an aphid. Geminiviruses are plant pathogens causing economically important diseases in most tropical and subtropical regions of the world. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the taxonomy of the Geminiviridae which is available at www.ictv.global/report/geminiviridae.